2022
DOI: 10.3389/fendo.2022.1026059
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the invasiveness of PTMC by a combination of ultrasound and the WNT10A gene

Abstract: ObjectiveThe purpose of this study was to predict the invasiveness of papillary thyroid microcarcinoma (PTMC) via ultrasonography in combination with the Wnt family member 10A (WNT10A) gene to provide a reference basis for evaluating the invasive capability of PTMC.MethodsCancer tissue were collected from 182 patients with unifocal PTMC, and the patients were divided into the invasive group and the non-invasive group based on whether the lesions invaded the thyroid capsules or whether lymph node metastasis occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Zhang et al . 99 observed higher WNT10A expression levels in the invasive PTMC group than those in the noninvasive group, and multivariate analysis indicated that high WNT10A expression constituted a risk factor for tumor aggressiveness in PTMC patients.…”
Section: Molecular Features Of Progressive Ptmcmentioning
confidence: 84%
“…Zhang et al . 99 observed higher WNT10A expression levels in the invasive PTMC group than those in the noninvasive group, and multivariate analysis indicated that high WNT10A expression constituted a risk factor for tumor aggressiveness in PTMC patients.…”
Section: Molecular Features Of Progressive Ptmcmentioning
confidence: 84%
“…However, there are few preoperative evaluations of the clinical high risk of PTMC. Yan Z [13] predicted the invasiveness of PTMC by combining ultrasound and the WNT10A gene. Their research showed that risk factors for PTMC invasiveness include age < 45 years old, maximum nodule diameter > 7 mm, microcalci cation, and high expression of US-LNM and WNT10A.…”
Section: Discussionmentioning
confidence: 99%